KAJIAN FILOLOGI DAN KEARIFAN BUDAYA LOKAL DALAM TEKS MANUSKRIP KEISLAMAN LAYANG IMAN SUJANA KOLEKSI ANUT EKOWIYONO - Rohmah, Nurul Baiti; Rejo, Uman (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
This research describes the Islamic manuscript text Layang Iman Sujana with philological studies and local cultural wisdom. Layang Iman Sujana is a collection of Islamic manuscript texts collected by Anut Ekowiyono which contains the journey of the figure Iman Sujana from the country of Ngesam to spread the religion of Islam. This research aims to determine the study of philology and the study of local cultural wisdom in the Islamic manuscript text Layang Iman Sujana. This research is research using philological methods and is linked to local knowledge theory with the Tri Hita Karana cosmological concept. The results of the research show that Layang Iman Sujana generally tells the story of the character Iman Sujana who spread Islam on the orders of his father, Abdur Asfar. The local cultural wisdom contained in Layang Iman Sujana consists of two categories, namely harmonizing the relationship between people and God and harmonizing the relationship between people and each other. Harmonization of people with God in the form of sahadat, sharia, dhikr, surrender, torekot, prayer, quran, eling, piwales, titah, sukur, nugraha, and compassion. Meanwhile, the harmonization of humans with fellow humans takes the form of urmat, panuwun, ngabekti, tumindak becik, uluk salam, ngajeni, bale homestead, manners, nyenengke others, confident, combing anger, empan plank, and compassion.